Switching tax structure and payouts in endogenous bankruptcy models. Issue 2 (17th February 2016) - Barsotti, Flavia; Mancino, Maria Elvira; Pontier, Monique
Abstract : In the spirit of Leland (H.E. Leland, Corporate Debt Value, Bond Covenant, and Optimal Capital Structure, J. Finance 49 (1994), pp. 1213–1252), we consider a structural credit risk model with tax provisions under the assumption of a positive payout rate. By defining a more general tax structure than in (Leland, 1994), we introduce a general switching corporate tax rate function and analytically derive the value of the tax benefits claim, the whole capital structure and the smooth pasting condition. In this set-up, the endogenous failure level is derived and both the singular and joint effect of the two introduced risk factors (payouts and tax asymmetry) on optimal managerial financing decisions are studied. Results show a quantitatively significant impact on optimal debt issuance and leverage ratios, bringing them to values more in line with historical norms and providing a way to explain differences in observed leverage across firms.